Loading of a continuous anion beam into a Penning trap with a view to laser cooling - Cerchiari, Giovanni; Erlewein, Stefan; König, Charlotte; Kellerbauer, Alban (Physical review, 2018)
The capture and confinement of a large and pure sample of anions into an ion trap is challenging due to the fragile nature of these weakly bound atomic systems. We present the results of an experimental study using Au− in which anions from a keV-energy continuous beam were loaded into a cylindrical Penning trap. Experimental parameters such as stopping potential and axial trap depth were found to be crucial. The transfer of axial to radial momentum due to ion-ion collisions was identified as a main contributing factor to successful capture. A total number of up to 107Au− ions were loaded. The cooling of anions by simultaneously confined electrons was observed and seen to result in centrifugal separation of the two species. After storage times of several 10 s, electron cooling of the anions to the temperature of the cryogenic trap was achieved.